Microbiological Safety of Kitchen Sponges Used in Food Establishments - Wolde, Tesfaye (Int J Food Sci, 2016)
Kitchen sponges are among the possible sources of contaminants in food establishments. The main purpose of the current study was, therefore, to assess the microbiological safety of sponges as it has been used in selected food establishments of Jimma town. Accordingly, the microbiological safety of a total of 201 kitchen sponges randomly collected from food establishments was evaluated against the total counts of aerobic mesophilic bacteria (AMB), Enterobacteriaceae, coliforms, and yeast and molds. The mean counts of aerobic mesophilic bacteria ranged from 7.43 to 12.44 log CFU/mm(3). The isolated genera were dominated by Pseudomonas (16.9%), Bacillus (11.1%), Micrococcus (10.6%), Streptococcus (7.8%), and Lactobacillus (6%) excluding the unidentified Gram positive rods (4.9%) and Gram negative rods (9.9%). The high microbial counts (aerobic mesophilic bacteria, coliforms, Enterobacteriaceae, and yeast and molds) reveal the existence of poor kitchen sponge sanitization practice. Awareness creation training on basic hygienic practices to food handlers and periodic change of kitchen sponges are recommended.